Estrogen induces two distinct cholesterol crystallization pathways by activating ERα and GPR30 in female mice - de Bari, Ornella (J Lipid Res, 2015)
To distinguish the lithogenic effect of the classical estrogen receptor α (ERα) from that of the G protein-coupled receptor 30 (GPR30), a new estrogen receptor, on estrogen-induced gallstones, we investigated the entire spectrum of cholesterol crystallization pathways and sequences during the early stage of gallstone formation in gallbladder bile of ovariectomized female wild-type, GPR30((−/−)), ERα((−/−)), and GPR30((−/−))/ERα((−/−)) mice treated with 17β-estradiol (E(2)) at 6 µg/day and fed a lithogenic diet for 12 days. E(2) disrupted biliary cholesterol and bile salt metabolism through ERα and GPR30, leading to supersaturated bile and predisposing to the precipitation of cholesterol monohydrate crystals. In GPR30((−/−)) mice, arc-like and tubular crystals formed first, followed by classical parallelogram-shaped cholesterol monohydrate crystals. In ERα((−/−)) mice, precipitation of lamellar liquid crystals, typified by birefringent multilamellar vesicles, appeared earlier than cholesterol monohydrate crystals. Both crystallization pathways were accelerated in wild-type mice with the activation of GPR30 and ERα by E(2). However, cholesterol crystallization was drastically retarded in GPR30((−/−))/ERα((−/−)) mice. We concluded that E(2) activates GPR30 and ERα to produce liquid crystalline versus anhydrous crystalline metastable intermediates evolving to cholesterol monohydrate crystals from supersaturated bile. GPR30 produces a synergistic lithogenic action with ERα to enhance E(2)-induced gallstone formation.